2013
DOI: 10.1186/1471-2407-13-53
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cervical infection with HPV type 16 and 18 in Vietnam: implications for vaccine campaign

Abstract: BackgroundThe Expanded Program on Immunization currently considers offering Human Papilomavirus vaccine on a routine basis in Vietnam. However, as the current available vaccine can prevent only two types HPV 16 and 18, before implementing a large-scale vaccine campaign we need information about the prevalence of infection with only HPV 16 and 18 in Viet Nam. This study was done in 5 large cities in Vietnam to estimate the prevalence of HPV 16 and/or 18 infections and to explore the distribution of other high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 14 publications
4
29
0
Order By: Relevance
“…There are a number of variants such as monovalent (HPV16), bivalent (HPV16 and 18), quadrivalent (HPV6, 11, 16 and 18) and nonavalent (HPV6, 11,16,18,31,33, 45, 52 and 58) vaccines (5,6). In Vietnam, the measures for cervical cancer prevention include, primary screening for HPV and vaccination against HPV (7). It has been shown that there are differences in the genotype distribution in women with multiple HPV infections not only among women of different ethnicity but also women from different regions (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of variants such as monovalent (HPV16), bivalent (HPV16 and 18), quadrivalent (HPV6, 11, 16 and 18) and nonavalent (HPV6, 11,16,18,31,33, 45, 52 and 58) vaccines (5,6). In Vietnam, the measures for cervical cancer prevention include, primary screening for HPV and vaccination against HPV (7). It has been shown that there are differences in the genotype distribution in women with multiple HPV infections not only among women of different ethnicity but also women from different regions (8).…”
mentioning
confidence: 99%
“…Knowledge about the type-specific distribution and the prevalence of HPV cervical infection in women from diverse areas and ethnicity is a prerequisite for the planning of an efficient and adequate screening and vaccination strategy with the best possible outcome. Some studies have been conducted within Vietnam, especially in Ho Chi Minh City and Hanoi (7,(9)(10)(11), but also in populations from Thai Nguyen, Hue and Can Tho (9). These studies showed a prevalence of high-risk HPV infection, ranging between 2-11%.…”
mentioning
confidence: 99%
“…E7-LLMGTLGIV82-90 was known to induce the cellular response in HLA A2.1 rabbit model [39] and reduced tumor burden in aged mice [40]. E6-KLPDLCTEL13-22 [41] and E7-TLQDIVLHL [7][8][9][10][11][12][13][14][15] One of the predicted peptides, QLFVTVVDT [42] were proved to be CTL epitopes for HPV 18.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, two vaccines (Ceravix and Gardasil) are commercially administrated to prevent HPV infection [46]. These preventative vaccines are mainly used for protection against HPV type 16, 18, 6 and 11 [7]. Administration of these vaccines in some cases leads to severe side effects [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among high-risk HPV genotypes, HPV-16 and-18, which is identified as the common high-risk HPV genotypes and being the key role for the majority of cervical cancer (CC), counting for approximately 70.0% [5][6][7][8][9]. In Vietnam, the prevalence of cervical infection with HPV-16 and/or-18 among women was ranged from 3.1% to 7.4% [10]. Notably, the infection of high-risk HPV genotypes is considered as not exclusive prerequisites for cervical carcinogenesis [11].…”
Section: Introductionmentioning
confidence: 99%